Entospletinib monotherapy in patients with relapsed or refractory chronic lymphocytic leukemia previously treated with B-cell receptor inhibitors: results of a phase 2 study. Issue 8 (3rd July 2019) - Awan, Farrukh T.; Thirman, Michael J.; Patel-Donnelly, Dipti; Assouline, Sarit; Rao, Arati V.; Ye, Wei; Hill, Brian; Sharman, Jeff P.
Abstract: Entospletinib (GS-9973), an oral, selective inhibitor of spleen tyrosine kinase (SYK), was evaluated as monotherapy in this multicenter, phase 2 study (NCT01799889) of 49 patients with relapsed or refractory chronic lymphocytic leukemia (CLL), including those with Richter's transformation (RT), who had received prior therapy with a B-cell receptor (BCR) inhibitor. Patients were treated with entospletinib 400 mg BID as the starting dose. Sixteen patients achieved partial response and 21 had stable disease. The overall response rate was 32.7% (95% confidence interval [CI]: 21.7–45.3%). The median progression-free survival (PFS) was 5.6 (95% CI: 3.7–8.3) months. Twenty-one (of 43) patients (48.8%) experienced nodal response. Adverse events (AEs) occurred in all patients; most commonly fatigue, diarrhea, and anemia. Entospletinib monotherapy has clinical activity for patients with CLL and RT who have relapsed following therapy with BCR inhibitors.